Proline catalyzed sequential alpha-amination/ Prins/ Ritter amidation of aldehydes: new method of construction of tetrahydropyran units - Ahuja, Brijbhushan; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient ``one-pot'' synthetic method toward highly substituted tetrahydrofuran (THP) units is reported. The key transformation involves an atom-efficient sequential proline catalyzed alpha-amination of aldehydes to give alpha-aminated aldehydes in situ and the subsequent cyclomerization with homoallylic alcohols under Prins/Ritter conditions. Notably, this method provides access to enantiopure 1,2-syn and 1,4-anti diamino alcohols via reductive ring opening of THP units.
Keywords: alpha-aminoxylation; organocatalysis; Proline catalyzed; sequential; tetrahydropyran unit